Electrospinning of 3D scaffold - Tee, Chong Yen. (2010)
Two common problems in the fabrication of tissue engineered scaffolds using electrospinning techniques are poor cellular infiltration into the scaffold and thin dimension of the scaffold which limits its application. In this work, we proposed a novel method to fabricate 3D scaffold to address these issues. We also suggest to further enhance the properties of our scaffold by surface modifying it. The novel method which we employed to produce our 3D scaffold was a modified electrospinning technique. Scaffold was collected on a needle rather than a flat collector plate. A spherical scaffold with diameter approximately 1.5cm could be collected in half an hour time. Scaffold was then surface modified to incorporate gelatin onto the scaffold. The contact angle testing showed that surface modified scaffold had an extremely high hydrophilicity with 0° contact angle compared to non modified scaffold with 111.60° contact angle. Furthermore, mercury porosimetry test showed that the scaffold produced by our method had pores with diameters over 50μm and porosity of over 90%. These characteristic allowed our scaffold to achieve cell infiltration depth of more than 5mm or 100% cell infiltration. This level of cell infiltration had never been reported in any of the research paper yet.